Impairment of Dendrodendritic Inhibition in the Olfactory Bulb of APP/PS1 Mice - Li, Weiyun; Li, Shanshan; Shen, Lianghua; Wang, Junbo; Wu, Xuewei; Li, Jing; Tu, Chunlong; Ye, Xuesong; Ling, Shucai (Frontiers in Aging Neuroscience, 2019)
Olfactory dysfunction is an early event in Alzheimer’s disease (AD). However, the mechanism underlying the AD-related changes in the olfactory bulb (OB) remains unknown. Granule cells (GCs) in the OB regulate the activity of mitral cells (MCs) through reciprocal dendrodendritic synapses, which is crucial for olfactory signal processing and odor discrimination. Nevertheless, the relationships between the morphological and functional changes of dendrodendritic synapses, particularly the local field potentials (LFPs) as a consequence of olfactory disorders in patients with AD have not been investigated. Here, we studied the morphological and functional changes induced by dendrodendritic inhibition in GCs onto MCs in the OB of amyloid precursor protein (APP)/PS1 mice and age-matched control mice during aging, particular, we focused on the effects of olfactory disorder in the dendrodendritic synaptic structures and the LFPs. We found that olfactory disorder was associated with increased amyloid-β (Aβ) deposits in the OB of APP/PS1 mice, and those mice also exhibited abnormal changes in the morphology of GCs and MCs, a decreased density of GC dendritic spines and impairments in the synaptic interface of dendrodendritic synapses between GCs and MCs. In addition, the aberrant enhancements in the γ oscillations and firing rates of MCs in the OB of APP/PS1 mice were recorded by multi-electrode arrays (MEAs). The local application of a GABAAR agonist nearly abolished the aberrant increase in γ oscillations in the external plexiform layer (EPL) at advanced stages of AD, whereas a GABAAR antagonist aggravated the γ oscillations. Based on our findings, we concluded that the altered morphologies of the synaptic structures of GCs, the dysfunction of reciprocal dendrodendritic synapses between MCs and GCs, and the abnormal γ oscillations in the EPL might contribute to olfactory dysfunction in AD.